2017
DOI: 10.1148/radiol.2017160622
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between Hepatic Inflammation and Fibrosis with MR Elastography

Abstract: Purpose To investigate the utility of Magnetic Resonance Elastography (MRE)-derived mechanical properties in discriminating hepatic inflammation and fibrosis in the early stages of chronic liver diseases. Material and Methods All studies were approved by our institutional animal care and use committee. A total of 187 animals were studied, including 182 mice and 5 pigs that represent five different liver diseases with a varying combination and extent of hepatic inflammation, fibrosis, congestion and portal hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
139
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 35 publications
5
139
1
Order By: Relevance
“…Interestingly, liver stiffness has been found in some cases to be correlated to mesenteric blood flow and portal venous blood flow . This dependence on hemodynamic parameters was also observed in a small‐animal study at 3.0 T …”
Section: Validation Studiessupporting
confidence: 63%
“…Interestingly, liver stiffness has been found in some cases to be correlated to mesenteric blood flow and portal venous blood flow . This dependence on hemodynamic parameters was also observed in a small‐animal study at 3.0 T …”
Section: Validation Studiessupporting
confidence: 63%
“…Compared with 2D‐MRE, 3D‐MRE allows a more comprehensive analysis of the steady‐state dynamic shear wave propagation in the entire liver . In mouse models of diet‐induced NASH, the damping ratio and shear loss modulus have been shown to enable discrimination of inflammation from fibrosis at early stages of disease, even before the development of histologically detectable necroinflammation and fibrosis . These data represent a strong scientific premise that warrants investigation of MRE as an imaging biomarker for the noninvasive detection of NASH in humans.…”
mentioning
confidence: 99%
“…Liver stiffness generally consists of elasticity and viscosity, and intrahepatic hemodynamic changes, such as inflammation, congestion, and portal hypertension . The utility of multifrequency MRE is emerging as an interest for the separation of fibrosis from inflammation of the liver by calculating multiple parameters including loss modulus and damping ratio . However, preliminary clinical results demonstrated no additional value of multifrequency MRE for staging liver fibrosis compared with single‐frequency MRE .…”
Section: Discussionmentioning
confidence: 99%
“…This may be because stiffness value at 80‐Hz more strongly emphasizes dispersion of elastic waves in viscous media compared with that at 60‐Hz on MRE . A previous study showed that the loss modulus at high frequency has the potential to be used to assess necroinflammation . The ΔG could emphasize the residual viscous factor in the liver parenchyma, which is associated with histological inflammation.…”
Section: Discussionmentioning
confidence: 99%